2010
DOI: 10.1039/c0jm01903h
|View full text |Cite
|
Sign up to set email alerts
|

Photo-response behavior of electrospun nanofibers based on spiropyran-cyclodextrin modified polymer

Abstract: Tunable and durable photochromic materials are a rapidly expanding area of interest, with applications ranging from biomedical devices to industrial-fields. Here we examine electrospun poly (methacrylic acid) PMAA nanofibers covalently modified with the highly photochromic molecule, spiropyran (SP) or a derivate SP which is firstly coupled to a cyclodextrin molecule (βCDSP). The photochromic properties of the starting materials and of the nanofibers were investigated. βCDSP, PMAASP and PMAA-βCDSP polymers exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 59 publications
1
32
0
Order By: Relevance
“…The most representative example of the open-closed ring transition is spiropyran (SP) and its derivatives. Sousa et al [129] showed the fabrication of electrospun poly(methacrylic acid) nanofibers and further covalently modified the nanofibers with SP or cyclodextrin-SP inclusion complex. The photo-reversibility of the nanofibers was verified by recurrent exposure to visible and UV light and measuring water contact angles on the surface.…”
Section: Stimuli-responsive Electrospun Nanofibers For Controlled Relmentioning
confidence: 99%
See 1 more Smart Citation
“…The most representative example of the open-closed ring transition is spiropyran (SP) and its derivatives. Sousa et al [129] showed the fabrication of electrospun poly(methacrylic acid) nanofibers and further covalently modified the nanofibers with SP or cyclodextrin-SP inclusion complex. The photo-reversibility of the nanofibers was verified by recurrent exposure to visible and UV light and measuring water contact angles on the surface.…”
Section: Stimuli-responsive Electrospun Nanofibers For Controlled Relmentioning
confidence: 99%
“…They assumed that such changes in wettability arose not only from the azo surface functionalization but also from the roughness intrinsically offered by the electrospun nano/microscale hierarchical structures. Interestingly, the only existing drug-release experiment of L-RDLEF was published by Fu et al [131], two years ahead of Sousa [129] and Chen [130]. They fabricated poly(vinylbenzyl chloride -glycidyl methacrylate) (PVBC- b -PGMA) nanofibers by electrospinning (Fig.…”
Section: Stimuli-responsive Electrospun Nanofibers For Controlled Relmentioning
confidence: 99%
“…The organic molecule in the MHM should present specific characteristics in order to improve the material application, including available binding sites, to bond or interact through intermolecular forces with the inorganic matrix, and high surface area, which is important to improve the MHM adsorption and adhesion properties. In order to design a MHM based on Fe-Ni/Zn with adsorption properties for environmental use, cyclodextrins (CDs) can be associated with the inorganic matrix as an interesting strategy, since these macromolecules have been used for several devices with different properties, from light-responsive matrices to molecular recognition materials [1213]. …”
Section: Introductionmentioning
confidence: 99%
“…The corresponding maximum absorption intensities were measured immediately after each irradiation by UV–vis spectrophotometer. Figure displays that the maximum absorption intensities of NFMs had a slight reduction after 20 cycles . This could be ascribed to the excellent protection of the comb‐polymer nanoparticles for photochromic molecules.…”
Section: Resultsmentioning
confidence: 90%
“…The isomeric MC form appears amaranth, with an intense visible absorption peak in the range of 500–520 nm. And after stopping the UV irradiation or exposing to a visible light, a reversible transformation from colored MC form to colorless SP form will occur . Despite its safety and efficacy, spiropyran suffers from several major limitations in its application.…”
Section: Introductionmentioning
confidence: 99%